2016
DOI: 10.1186/s40981-016-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

A case of hemothorax due to traumatic bleeding managed effectively by Sonoclot®-guided blood transfusion

Abstract: A 71-year-old woman was transported to our hospital due to traumatic bleeding, and an operation was immediately performed for achieving hemostasis. We decided to perform Sonoclot®-guided blood transfusion. When Sonoclot signatures had returned normal values, further bleeding did not occur. We experienced the first case of traumatic bleeding managed effectively by using Sonoclot. We suggest that a Sonoclot analyzer may be useful for the management of severe coagulopathy due to traumatic bleeding like ROTEM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The Sonoclot analyzer has been traditionally employed in liver transplantat surgery, cardiovascular surgery, neurosurgery and other surgeries involving significant bleeding volume. Lately, it is also used in intensive care of pregnant women and children [ [6] , [7] , [8] , [9] ]. Here, we investigated the feasibility of applying Sonoclot in the diagnosis of PE.…”
Section: Introductionmentioning
confidence: 99%
“…The Sonoclot analyzer has been traditionally employed in liver transplantat surgery, cardiovascular surgery, neurosurgery and other surgeries involving significant bleeding volume. Lately, it is also used in intensive care of pregnant women and children [ [6] , [7] , [8] , [9] ]. Here, we investigated the feasibility of applying Sonoclot in the diagnosis of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that Sonoclot might predict postoperative hemorrhage in cardiac surgery [ 19 , 20 ]. We have previously demonstrated the usefulness of Sonoclot as a transfusion strategy in cases of massive bleeding in trauma [ 21 ]. The operating cost of the Sonoclot is more efficient than that of other devices, which is a strong advantage in the Japanese insurance system [ 16 ].…”
Section: Introductionmentioning
confidence: 99%